2020
DOI: 10.1055/s-0040-1713825
|View full text |Cite
|
Sign up to set email alerts
|

Goniometric Evaluation and Passive Range of Joint Motion in Chondrodystrophic and Non-Chondrodystrophic Dogs of Different Sizes

Abstract: Objective This study aimed to evaluate angle values in maximal flexion and extension; the passive range of motion (PROM) of the shoulder, elbow, carpal, hip, stifle and tarsus; and the carpal abduction and adduction of chondrodystrophic (CD) and non-chondrodystrophic (NCD) dogs of different sizes. Study Design Goniometric evaluation was performed in triplicate using a universal goniometer. CD dogs were categorized into miniature, small, medium, large and giant sizes, whereas NCD dogs were allocated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…Clinical studies have shown that surgical tendonectomy of the ADIL-tendon can lead to the development of carpal osteoarthritis, suggesting that the ADIL-tendon contributes to carpal stability (Grundmann & Montavon, 2001;Harasen, 2010). In this regard, a higher frequency of absence of the sesamoid bone in small dog breeds is indicative of a mechanical influence on the development of this sesamoid bone, the mechanical load on the ADILmuscle and carpus in these breeds being different from that of larger breeds (Reusing, Brocardo, Weber, & Villanova, 2020). If the presence or absence of (mineralization of) the sesamoid bone were due to mere mechanical loading, the sesamoid bone could be expected to be (radiologically) absent in more breeds belonging to the small breed group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have shown that surgical tendonectomy of the ADIL-tendon can lead to the development of carpal osteoarthritis, suggesting that the ADIL-tendon contributes to carpal stability (Grundmann & Montavon, 2001;Harasen, 2010). In this regard, a higher frequency of absence of the sesamoid bone in small dog breeds is indicative of a mechanical influence on the development of this sesamoid bone, the mechanical load on the ADILmuscle and carpus in these breeds being different from that of larger breeds (Reusing, Brocardo, Weber, & Villanova, 2020). If the presence or absence of (mineralization of) the sesamoid bone were due to mere mechanical loading, the sesamoid bone could be expected to be (radiologically) absent in more breeds belonging to the small breed group.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a chondrodystrophic breed as the French bulldog demonstrates such a low prevalence rate of the sesamoid bone. Chondrodystrophic dogs of particularly the small breed group exhibit a greater range of carpal motion compared to non-chondrodystrophic dogs, attributed to the characteristic angular deformity of the carpus (Reusing et al, 2020) and different leverage during rotation due to the relatively shorter leg (Fischer & Lilje, 2014;Roos, Brugger, & Rauscher, 1992). Furthermore, the dysplastic, shortened long bones in chondrodystrophic dogs are the result of a genetic defect that results in a disturbed endochondral ossification (Brown et al, 2017;Dickinson & Bannasch, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, postoperative evaluation was based on the joint angle of the contralateral limb, which was considered normal in each case. [23][24][25][26] After removal of the ESF, goniometry showed that the carpal joint angles in these two dogs were each approximately 15 in extension in the standing position, which was very similar to the joint angles of their contralateral limbs, suggesting that the carpal joint angles had been returned to normal. Furthermore, ultrasonography performed 3 months after surgery in both dogs showed that the structure and thickness of the repaired FCU appeared to be similar to that of the unaffected limb, suggesting that the transplanted fascia may have helped to restore normal function.…”
Section: Discussionmentioning
confidence: 99%
“…Passive joint range of motion (n = 3) and kinematic analysis (n = 3) were the most common methods used to evaluate changes in stiffness [19,23,[28][29][30][31]. While measures of normal passive joint range of motion has been reported for the appendicular skeleton [44,65], similar measures are not readily available within the axial skeleton due to a diverse array of measurement methods for assessing spinal stiffness [66].…”
Section: Outcome Parametersmentioning
confidence: 99%